2023
DOI: 10.1002/ecs2.4500
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal overlap with invasive wild pigs (Sus scrofa) varies by species and season in a temperate ecosystem

Abstract: Wild pigs (Sus scrofa), which are invasive in many regions globally, can alter ecosystems and compete with native species through interference competition and resource exploitation. Wild pig impacts on other species may increase with greater niche overlap, which could vary over time based on environmental conditions, resource availability, or biological traits like diet, especially as seasonal variation in wild pig diet has been widely documented. A limited number of studies have assessed spatial or temporal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Of our focal species, gray foxes were likely at the highest risk of predation by coyotes, considering coyote-specific mortality is well documented (e.g., Fedriani et al, 2000) and we observed gray foxes killed by coyotes in our study area. This may also explain why we did not detect red foxes at our carcasses, despite them being present in our study area (Saldo et al, 2023): predation risk from coyotes may be even greater for red foxes (Levi & Wilmers, 2012). We also found that bobcats fed more when understory cover was minimal.…”
Section: How Forest Structure Influenced Scavenging and Mediated Riskmentioning
confidence: 67%
See 1 more Smart Citation
“…Of our focal species, gray foxes were likely at the highest risk of predation by coyotes, considering coyote-specific mortality is well documented (e.g., Fedriani et al, 2000) and we observed gray foxes killed by coyotes in our study area. This may also explain why we did not detect red foxes at our carcasses, despite them being present in our study area (Saldo et al, 2023): predation risk from coyotes may be even greater for red foxes (Levi & Wilmers, 2012). We also found that bobcats fed more when understory cover was minimal.…”
Section: How Forest Structure Influenced Scavenging and Mediated Riskmentioning
confidence: 67%
“…We stratified carcass deployment locations based on coyote activity. We primarily used data from an established camera array in our study area (Saldo et al, 2023) to estimate coyote activity (Appendix S1). The array consisted of ~90 unbaited cameras deployed on dirt roads, each ~1 km apart (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…For blackberries, we established plots along dirt roads in our study area, in which we counted the number of ripe blackberries each week. We established four plots per site, and each site was associated with an existing wildlife camera in a 1 km 2 array (Saldo et al., 2023 ). We made sure to stratify our sites each year across various forest successional stages (early, middle, and late successional forest) because ripening timing could depend on the amount of sunlight blackberries get.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, we classified our each of our camera sites (Saldo et al., 2023 ) into four classes of vegetation (mature pines, immature pines, clear‐cut, mixed pine, and hardwood), then randomly chose one site from each class to count blackberries at. Once at the site, we set up four 3 x 1 m plots, in which we counted blackberries each week (Figure 2 ).…”
Section: Text A1: Description Of Methods Used To Capture and Collect ...mentioning
confidence: 99%